FRI0030 Synovial mast cells identify patients with a severe phenotype in a cohort of dmard naÏve patients with early rheumatoid arthritis. (15th June 2017) - Rivellese, F; Humby, F; Nerviani, A; Pagani, S; Mauro, D; Paulis, A de; Marone, G; Pitzalis, C
Abstract : Background: Mast cells (MCs) are among the immune cells participating to the inflammatory response in Rheumatoid Arthritis (RA), but their exact contribution to disease development and progression is unclear. Objectives: To evaluate the presence of MCs in the synovia of patients with early RA naïve to treatment and their correlation with baseline clinical phenotype, response to DMARDs and disease progression. Methods: DMARD-naïve patients with early (<12 months) RA (n=99) fulfilling the 2010 ACR/EULAR criteria were recruited as part of the Pathobiology of Early Arthritis Cohort at Barts Health NHS Trust. Sections of paraffin embedded synovial tissue obtained by ultrasound-guided synovial biopsy were stained by immunohistochemistry for CD117 (c-kit) and patients were classified into MC+ and MC- groups. Differences in clinical parameters at baseline and 6 months and progression in radiographic damage at 12 months were evaluated. The expression of Receptor Activator of Nuclear factor Kappa-B Ligand (RANKL) by human primary MCs was assessed by western blot and immunofluorescence. Results: The presence of synovial CD117+ MCs was significantly associated with highly active disease (DAS28, ESR, CRP, tender and swollen joint counts, p<0.05). At the 6 months follow-up, there were no differences in terms of response to treatment with synthetic DMARDs (e.g. DAS28 remission 38.8% in MC+ vs 42.9% in MC-, p=0.725). Nonetheless, MC+ patients showed a significantly higher prevalence of radiographic progression at 12 months (progressors/non progressors 13/38 in MC+ vs 0/28 in MC-, p=0.003, n=79). When progressors were compared with non progressors, there were no differences in clinical parameters at baseline (inflammatory markers, DAS28, ACPA or RF positivity). Because of the observed association of MCs with radiographic progression, we looked for mechanisms that could link MCs to bone erosions, and we found that human primary MCs express the osteoclast activator RANKL. Conclusions: We show that synovial MCs identify patients with a severe clinical phenotype in a DMARD-naïve early RA cohort. In particular, despite a similar rate of response to DMARDs at 6 months, the presence of synovial MCs at baseline was significantly associated with radiographic progression at 12 months. As clinical parameters at baseline showed no association with radiographic progression, our work suggests that the analysis of synovial MCs could help to identify patients at high risk of progression in radiographic damage, warranting further investigations to confirm the association of MCs with the development of joint damage and their direct contribution to bone erosion, possibly via a RANKL-mediated activation of osteoclasts. Disclosure of Interest: None declared